Biomaterial and Therapeutic Approaches for the Manipulation of Macrophage Phenotype in Peripheral and Central Nerve Repair - Adrian Dervan; Antonio Franchi; Francisco R. Almeida-Gonzalez; Jennifer K. Dowling; Ohemaa B. Kwakyi; Claire E. McCoy; Fergal J. O’Brien; Alan Hibbitts (Pharmaceutics, 2021)
Injury to the peripheral or central nervous systems often results in extensive loss of motor and sensory function that can greatly diminish quality of life. In both cases, macrophage infiltration into the injury site plays an integral role in the host tissue inflammatory response. In particular, the temporally related transition of macrophage phenotype between the M1/M2 inflammatory/repair states is critical for successful tissue repair. In recent years, biomaterial implants have emerged as a novel approach to bridge lesion sites and provide a growth-inductive environment for regenerating axons. This has more recently seen these two areas of research increasingly intersecting in the creation of ‘immune-modulatory’ biomaterials. These synthetic or naturally derived materials are fabricated to drive macrophages towards a pro-repair phenotype. This review considers the macrophage-mediated inflammatory events that occur following nervous tissue injury and outlines the latest developments in biomaterial-based strategies to influence macrophage phenotype and enhance repair.